WI2020 Zentrale Tracks 2020
DOI: 10.30844/wi_2020_g3-marheine
|View full text |Cite
|
Sign up to set email alerts
|

Governance Strategies to Drive Complementary Innovation in IoT Platforms: A Multiple Case Study

Abstract: The widespread uptake of the Internet of Things spurred both software and hardware firms to compete for platform leadership. Information systems research has acknowledged that a platform's success depends on the innovational output of its ecosystem of firms. However, the question whether platform owners should coordinate these firms through cooperative or competitive strategies to create complementary applications remains unaddressed. To address this gap, an exploratory, multiple case study of four German comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have explored the relationships between real-time visibility and the Internet of Things (de Vass et al, 2020;Fahim et al, 2021;Lee and Rim, 2016;Lee and Lee, 2015). Marheine (2020) did not attempt to explain how to unlock value from complementors and ensure successful platform execution and successful governance that can reduce the asymmetry effects and increase the willingness of complementors to manage the B2B IoT digital platforms successfully. Hein et al (2020) suggested from an ecosystem perspective, it is pivotal to understand how firms can integrate their existing network of stakeholders from a goods-dominant perspective of creating value to a services-dominant view of co-creating value.…”
Section: Research Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have explored the relationships between real-time visibility and the Internet of Things (de Vass et al, 2020;Fahim et al, 2021;Lee and Rim, 2016;Lee and Lee, 2015). Marheine (2020) did not attempt to explain how to unlock value from complementors and ensure successful platform execution and successful governance that can reduce the asymmetry effects and increase the willingness of complementors to manage the B2B IoT digital platforms successfully. Hein et al (2020) suggested from an ecosystem perspective, it is pivotal to understand how firms can integrate their existing network of stakeholders from a goods-dominant perspective of creating value to a services-dominant view of co-creating value.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The willingness of freight forwarders to exert control significantly contributes to tension competition versus collaboration in the relations between the freight forwarders and a platform owner. Other studies on the IoT platforms did not identify tensions (Marheine, 2020) but discussed governance strategies. The scholars call for research on how platforms balance seemingly conflicting tensions (e.g.…”
Section: Tensions On Unfinished Pathsmentioning
confidence: 99%
See 2 more Smart Citations